Undergraduate students' profile based on attitudes towards statistics - Mansor, R.; Zaini, B.J.; Yusof, Z.M.; Darmesah Gabda; Wong, W. (Akademi Sains Malaysia, 2020)
The purpose of this study was to investigate students' profiles based on their attitudes towards statistics in Universiti Utara Malaysia. This study adopted a quantitative survey design. The questionnaires were administered on a sample of 274. The Stratified sampling method was used to generate the sample. The methodologies used were descriptive statistics, factor analysis and statistical test to compare between demographic factors such as gender, race, and qualification. Findings revealed that seven factors that explain the attitude of the students were self-determination, cognitive competence, effort, a value of statistics in professional life, difficulty, statistical solving and value of statistics in everyday life. The results of the descriptive statistical analyses found that students have a positive attitude towards statistics. The finding suggested that statistics should be revealed more practically to developing a more positive attitude towards statistics can further promote the learning process and students' ability to apply the concepts. © 2020.